Charles Wilkes papers - Wilkes, Charles, 1798-1877.
Correspondence, letterbooks, journals and diaries, autobiography, scientific tracts and notes detailing weather and tidal observations, legal and financial papers, genealogical charts, printed material, and other papers. Subjects include Wilkes's command of an expedition (1838-1842) to the Antarctic, islands in the Pacific, and the northwest coast of the U.S.; his work in Washington, D.C., preparing and publishing (1843-1863) information collected by the expedition; his capture of J.M. Mason and John Slidell in the Trent affair (1861); and his command of the James River Flotilla and the West India Squadron during the Civil War. Subjects include efforts to capture Confederate destroyers, commerce in the North, and dissatisfaction with American leadership during the Civil War; and an outbreak of cholera in Germany in 1873. Also includes letterbooks (1817-1841) of William Compton Bolton. Correspondents include Louis Agassiz, James Dwight Dana, Joseph Drayton, Asa Gray, George Brinton McClellan, Fred D. Stuart, and Gideon Welles.
Family papers include correspondence of Charles Wilkes, his children John, Jane, and Eliza, and his wives Jane Renwick Wilkes and Mary Lynch Bolton Wilkes; genealogies; and marriage and building contracts, leases, inventories, promissory notes, trust agreements, and debt records dating from the seventeenth century concerning the family in England and America.
Microfilm edition of containers 1-31 available
Microfilm produced from originals in the Manuscript Division.
Naval officer and explorer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agassiz, Louis, -- 1807-1873 -- Correspondence; Bolton, William Compton, -- -1849 -- Correspondence; Dana, James Dwight, -- 1813-1895 -- Correspondence; Drayton, Joseph -- Correspondence; Gray, Asa, -- 1810-1888 -- Correspondence; Mason, J. M. -- 1798-1871.; McClellan, George Brinton, -- 1826-1885 -- Correspondence; Slidell, John, -- 1793-1871.; Stuart, Fred D. -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; Wilkes, Eliza -- Correspondence; Wilkes, Jane -- Correspondence; Wilkes, Jane Renwick, -- -1843 -- Correspondence; Wilkes, John, -- 1827-1908 -- Correspondence; Wilkes, Mary Lynch Bolton -- Correspondence; Wilkes family; Confederate States of America. -- Navy; United States. -- Navy. -- James River Flotilla; United States. -- Navy. -- Potomac Flotilla; United States. -- Navy. -- West India Squadron; Astronomy; Cholera -- Germany; Maps; Meteorology -- Observations; Scientific expeditions -- Antarctica; Scientific expeditions -- Hawaii; Scientific expeditions -- Oceania; Tides; Trent Affair, 1861.; Antarctica -- Discovery and exploration; Hawaii -- Discovery and exploration; Oceania -- Discovery and exploration; United States -- Commerce; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- Politics and government -- 1861-1865.; Explorers; Naval officers